An exploration of testosterone levels in patients with bipolar disorder. Issue 2 (October 2015) - Wooderson, Sarah C.; Gallagher, Peter; Watson, Stuart; Young, Allan H.
Abstract : Background: Testosterone influences well-being, mood and cognition and may play a role in the pathophysiology of bipolar disorder. Aim: To examine testosterone levels in patients with bipolar disorder compared with healthy controls. Method: We examined baseline total testosterone levels and current depression scores in male and female patients with bipolar disorder and mild to moderate depression and healthy controls. Results: A significant interaction between diagnosis and gender was observed ( F (2, 97)=9.791, P =0.002). Testosterone levels were significantly lower for male patients with bipolar disorder compared with male controls ( P =0.001). Women with bipolar disorder had significantly higher testosterone levels than female controls ( P =0.03). Conclusions: Disturbances in testosterone levels may represent an important neurobiological abnormality in bipolar disorder and may differ by gender. If these findings are confirmed, the use of gender appropriate treatment strategies for the normalisation of testosterone levels in bipolar disorder depression should be further explored.